Fitting traffic traces with discrete canonical phase type distributions and Markov arrival processes - Mészáros, András; Papp, János; Telek, Miklós (Zielona Góra: Uniwersytet Zielonogórski)
Recent developments of matrix analytic methods make phase type distributions (PHs) and Markov Arrival Processes (MAPs) promising stochastic model candidates for capturing traffic trace behaviour and for efficient usage in queueing analysis. After introducing basics of these sets of stochastic models, the paper discusses the following subjects in detail: (i) PHs and MAPs have different representations. For efficient use of these models, sparse (defined by a minimal number of parameters) and unique representations of discrete time PHs and MAPs are needed, which are commonly referred to as "canonical representations".
Keywords: fitting traffic traces; discrete phase type distribution; discrete Markov arrival process; canonical representation